2022
DOI: 10.3846/btp.2022.13687
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Segmentation: Mobile Phone Purchase Vis-À-Vis Consumption Decision

Abstract: Prior studies intensively rely on lifestyle segmentation to investigate the patterns of purchase and consumption decisions. However, the literature does not specifically relate lifestyle profiles with the types of consumer decisions (i.e., purchasing vs. consumption decisions). Therefore, this research analyzed the issue by surveying 626 residents of Salatiga city, Indonesia, as the participants through self-administered questionnaires. By analyzing the data with factor, cluster, and chi-square analysis, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…One of the more intriguing developments in value methodology in recent years has been the Values and Life Style (VALS) methodology developed at SRI International by Mitchell (1983) based mainly on Maslow's (1954) need hierarchy and the concept of social character (Nugraha et al, 2022). Through statistical and theoretical means, 34 questions were identified as useful in classifying people into one out of nine lifestyle groups.…”
Section: Generic Value Classification Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the more intriguing developments in value methodology in recent years has been the Values and Life Style (VALS) methodology developed at SRI International by Mitchell (1983) based mainly on Maslow's (1954) need hierarchy and the concept of social character (Nugraha et al, 2022). Through statistical and theoretical means, 34 questions were identified as useful in classifying people into one out of nine lifestyle groups.…”
Section: Generic Value Classification Studiesmentioning
confidence: 99%
“…The shift in marketing approach from mass marketing to product-based marketing and then consumer-oriented marketing has highlighted the need for market segmentation (James et al , 2017). Marketers need to segment the market based on demographic, geographical and behavioral variables, thereby tailoring their marketing strategies and tactics to the target consumer segments (Sharma et al , 2020; Nugraha et al , 2022). By market segmentation, they divide the heterogeneous market into homogeneous subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the relationship between consumers' life style and consumption has become a meaningful academic topic, and various research results have been produced on specific issues related to life style, such as the relationship between life style and gender, economic income, health, and education [38][39][40][41]. It is found that there is no significant relationship between life style segmentation and product brand or country of origin when consumers make purchase decisions [42], but there are various factors that consumers consider when they make purchases. Besides branding, product attributes are also an important factor.…”
Section: The Influence Of Life Style On Consumptionmentioning
confidence: 99%